Theme of otherness and writing back: a cotrapuntal analysis of colonial and postcolonial novels - Orchi, Ridwana Kabir (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2009.